ANALISIS DESKRIPTIF MAKNA BUDAYA DALAM TARIAN TIDE-TIDE DI DESA TOBE KECAMATAN TOBELO SELATAN - Anwar Nada; Trihan O Mussy (Jurnal Bilingual, 2022)
The people of North Maluku, have customary procedures which are the identity of each tribe and each tribe has its own characteristics, such as in the social dance of the Galela-Tobelo tribe in the tide-tide dance. The characteristics of other tribes in North Maluku, and the focus of the researcher is the cultural meaning of the tide-tide dance of the Galela-Tobelo tribe. This tide-tide dance is performed by a group of male and female dancers. In addition, the tide-tide dance is accompanied by traditional music. This study aims to reveal the cultural meaning in the motion and properties of the tide-tide dance of the Tobelo-Galela tribe in Tobe Village, South Tobelo District. The method used is descriptive qualitative research, and the data collection techniques that the researcher uses are observation, refer to entangling skills (SLC), recording and disability techniques, interviews and documentation, as well as data analysis techniques used, namely; data reduction, data presentation, and conclusion. Matsumoto and Juang (in Sarwono, 2010: 60), argue that the reciprocal relationship between culture and language shows that no culture can be understood without understanding the language. Based on the analysis of the results of the research on the cultural meaning of the tide-tide dance in Tobe Village, South Tobelo District, namely: a. The movements include: (1) preparation for training, (2) preparing clothing, (3) dancers not wearing footwear, (4) hand movements, (5) foot movements, (6) face-to-face movements, (7) distance between dancers. While b. The properties used by dancers when performing the dance are divided into two parts, namely set properties and hand properties. The property set consists of: (1) damuru (tifa), (2) gongs, (3) kebaya, (4) sarong (skirt), (5) konde, (6) salempang (shawl), (7) white shirt, ( 8) trousers, (9) tuala (headband), (10) waistband. Meanwhile, Handproperty consists of (1) preparing clothes, (2) fiol (violin). There are several cultural meanings such as, religious/belief, social and scientific. Each has its own cultural meaning, and the most dominant cultural meaning is the meaning of social culture.